LFIs and methods of classical recapture. (27th November 2018) - Tajer, Diego
Abstract: In this paper, I will argue that Logics of Formal Inconsistency (LFIs) can be used as very sophisticated and powerful methods of classical recapture. I will compare LFIs with the well-known non-monotonic logics by Batens (2001, Log. Anal., 45–68) and Priest (2006, In Contradiction, Oxford University) and the 'shrieking' rules of Beall (2013, Rev. Symb. Log., 6, 755–764). I will show that these proposals can be represented in LFIs and that LFIs give room to more complex and varied recapturing strategies.